Memória roubada: teatralidades performáticas nas intervisualidades de Ana Maria Pacheco - Santos, Valéria Braga dos (2015)
The purpose of this work is to study Memória Roubada I (Sculpture, 2001) done by the plastic artist Ana Maria Pacheco, born in Goiânia, 1943. This sculpture condenses and opens new paths at the Brazilian art and their fictional representation of our memory. This artwork establishes more than a simple relationship between the parts. It enters the world as an intervention, which puts the viewer in the center of the perceptive action and allows multiple interpretations and experiences. This study aims enlarges questions and reflections with regard to dynamics of the perceptive act and the ability to formulate thoughts. It seeks to understand the complexity of Memória Roubada I, its domains and relationship to memory, history and cultural performances.